Differential Effects of Anxiety on Internet Gaming Disorder: A Large-Scale Cross-Sectional Survey - Huang, Xia; Shi, Hong-xia; Li, Hui-qin; Guo, Wan-jun; Luo, Dan; Xu, Jia-jun (Frontiers in Psychiatry, 2022)
Background: Internet gaming disorder (IGD) has become a serious public health problem in East Asia, and studies have reported IGD to be significantly associated with anxiety, but no causal relationship between the two has yet been demonstrated. Children are at high risk of developing IGD, however, previous studies have principally focused on the condition in adults and adolescents and reported non-clinical samples. A large-scale survey is needed to research and evaluate IGD and anxiety in children and adolescents to understand the current situation of IGD in children and explore the impact of IGD on anxiety. Methods: A cross-sectional study using an online questionnaire was conducted between March 1 and July 31, 2021. A total of 10,479 school children and adolescents in the western provinces of China were selected by convenience sampling. A questionnaire was used to collect data anonymously. The questionnaire covered IGD and the Revised Children's Manifest Anxiety Scale (RCMAS). Welch’s ANOVA Test and Games-Howell test were used to test for differences in anxiety levels between IGD groups. Poisson regression analysis was used to further investigate the key predictors of IGD. Results: 3.2% of participants (n=334) [95%CI:2.9–3.2%] were classified as at high risk of presenting with IGD, 71.1% (n=7454) [95%CI:70.3–72.0% ] were classified as low-risk players, and 25.7% (n=2691) [95%CI: 24.9–26.5%] were classified as non-gaming. The average RCMAS score was (7.18±7.534). The high-risk group had a higher total score RCMAS, as well as scoring higher in its three dimensions. Regression analysis using gender, age, and total RCMAS score as independent variables, and risk of IGD as a dependent variable showed that the odds ratio (OR) for gender was 2.864 [95%CI:2.267-3.618], and the OR for total RCMAS score was 1.101 [95%CI:1.087-1.114]. The OR for age was not statistically significant. Conclusion: Anxiety was a predictor of IGD, with statistically significant group differences in total anxiety, as well as the dimensions of physiological anxiety, social correlation, and sensitivity. The timely assessment of anxiety in children and adolescents, training social skills, and facilitating effective integration into society could be effective ways of reducing the incidence and impact of IGD.